Mobile-based Assignment Reminder Application for Students and Lecturers - Kukuh Yulian Santoso; Taufiq Abidin; Slamet Wiyono (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
This research is motivated by the large number of student activities that sometimes make students forget or overlook the activities they have to do on time. One of the activities that sometimes forget or even get overlooked is assignments. Assignments are activities carried out by a group of people in carrying out learning activities. The purpose of this study is to design an android-based task reminder application that can remind students about lecture assignments, be able to remember students about the deadline for assignment collection, and other information regarding lecture activities. The application design method used is the waterfall method. Research This study was tested using white-box and black-box methods. The test results show that the application is correct, has no errors in terms of logic and function, and can functionally produce the expected output.